Evaluation of the Tuberculosis Surveillance System in Depok, West Java - Aulia, Fitri; Helda; Nuh Ghazali Djadjuli, Hidayat (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
Depok is one of the cities with a high number of TB cases in West Java. The implementation of TB surveillance in Depok revealed challenges in meeting TB control indicators. Evaluating the surveillance system is essential to assess the quality of the existing system and identify barriers in TB surveillance implementation. Therefore, this study aims to evaluate TB surveillance system in Depok based on its components and attributes. This study was an assessment that describes the implementation of the TB surveillance system using both quantitative and qualitative approaches. It highlighted the systemic challenges that hindered effective TB control, such as inadequate knowledge of legal aspects, insufficient private-sector engagement, lack ability of data analysis and interpretation, the high percentage of TB officers who had not received the training was partly due to staff turnover, complex data collection, and low utilization of surveillance data for decision-making. To enhance the effectiveness of TB control efforts, this study recommends targeted training for healthcare workers, sufficient budget allocations, and simplified data management systems.